Management and Prevention of Saphenous Vein Graft Failure: A Review - McKavanagh, Peter; Yanagawa, Bobby; Zawadowski, George; Cheema, Asim (Cardiology and therapy, 2017)
Coronary artery bypass grafting (CABG) remains a vital treatment for patients with multivessel coronary artery disease (CAD), especially diabetics. The long-term benefit of the internal thoracic artery graft is well established and remains the gold standard for revascularization of severe CAD. It is not always possible to achieve complete revascularization through arterial grafts, necessitating the use of saphenous vein grafts (SVG). Unfortunately, SVGs do not have the same longevity, and their failure is associated with significant adverse cardiac outcomes and mortality. This paper reviews the pathogenesis of SVG failure, highlighting the difference between early, intermediate, and late failure. It also addresses the different surgical techniques that affect the incidence of SVG failure, as well as the medical and percutaneous prevention and treatment options in contemporary practice.